Prevalence of nomophobia and factors associated with it: a cross-sectional study - Khilnani, Ajeet Kumar; Thaddanee, Rekha; Khilnani, Gurudas (International Journal of Research in Medical Sciences, 2019)
Background: Excessive use of mobile phones, including smart phones, is found to result in various health related, social and psychological problems. Nomophobia expands to ‘No Mobile Phobia’, i.e., fear of being out of mobile phone contact. Previous studies on nomophobia have focused on the student populations, since the younger generation is more technology savvy. This questionnaire-based study aimed to know the prevalence and factors leading to nomophobia in general population. Methods: This study was conducted in western Gujarat from September 2018 to October 2018. A prevalidated questionnaire, containing three parts, the demographic details, details about the characteristics of mobile phone use and the Nomophobia Questionnaire (NMP-Q), was sent through emails and WhatsApp to 1000 individuals. The responses were tabulated and analyzed. Results: Out of 331 respondents 192 (58%) were males and 139 (42%) females. There was no significant difference in average NMP scores with respect to gender (p = 0.401), age brackets (p = 0.135), marital status (p = 0.123) and profession (p = 0.055). However, NMP scores were significantly more in individuals who spent more time on mobile phones per day (p = 0.000), checked their mobile phones more frequently (p<0.000) and in whom phantom ringing syndrome was also present (p<0.000). 241 respondents (72.80%) felt that their mobile phone use was consuming time and affecting their other daily activities. Conclusions: Nomophobia is an emerging health related adverse effect of prolonged mobile phone use. Interventions are required to promote judicious use of mobile phones.